Estruturação populacional de espécies de Drosofilídeos antófilas com diferentes graus de especialização - Carvalho, Tuane Letícia (2019)
Recently, the study of ecological specialization has become an important component for understanding the patterns related to the population dynamics of many species. Drosophilids associated with flowers are especially promising in studies of this type, since they present species with the most varied degree of ecological specialization, providing an opportunity for understanding the ecological and evolutionary mechanisms that promote the differentiation between populations and the emergence of new species. That said, this dissertation had the aim of promoting the understanding of the patterns and processes associated with the diversification of Drosophila anthophilic species. At first, we increased the know distribution of Drosophila alei in Brazil and characterized genetically, morphologically and ecologically the three species of the lutzii group occurring in the country; and in a second moment, we identified that the genetic variability and the population structure in species of the flavopilosa, bromeliae and lutzii group of Drosophila is not significantly associated with the degree of ecological specialization.